2023
DOI: 10.3390/pathogens12070922
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus and Borrelia burgdorferi Seroprevalence in Balkan Tick-Infested Individuals: A Two-Centre Study

Abstract: Lyme borreliosis (LB) and tick-borne encephalitis (TBE) are important tick-borne diseases in Europe. This study aimed to investigate the seroreactivity against Borrelia burgdorferi and TBE virus (TBEV) in tick-infested individuals in North Macedonia and Serbia. Serum samples were collected from tick-infested individuals and from healthy individuals in the same regions. Samples were tested for anti-Borrelia IgG reactivity and TBEV-neutralizing antibodies. Results showed higher seroreactivity against Borrelia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…In addition, TBEV-Nabs are only a subset of total anti-TBEV antibodies generated after exposure to TBEV. Although, TBEV-Nab seroprevalence in our cohort is higher compared to Norwegian, Romanian and Serbian blood donors (0.66 vs. 0.4% and 0.08 and 0%, respectively; Marvik et al, 2021 ; Coroian et al, 2022 ; Jakimovski et al, 2023 ) and much lower compared to residents of Czechia (0.66% vs. 26.3%; Kriz et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In addition, TBEV-Nabs are only a subset of total anti-TBEV antibodies generated after exposure to TBEV. Although, TBEV-Nab seroprevalence in our cohort is higher compared to Norwegian, Romanian and Serbian blood donors (0.66 vs. 0.4% and 0.08 and 0%, respectively; Marvik et al, 2021 ; Coroian et al, 2022 ; Jakimovski et al, 2023 ) and much lower compared to residents of Czechia (0.66% vs. 26.3%; Kriz et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 68%
“…However, a significant limitation of these studies is that TBEV exposure was inferred through assays not designed to differentiate anti-TBEV antibodies from the humoral response generated against other orthoflaviviruses circulating in Serbia (e.g., Orthoflavivirus usutuense and WNV). Indeed, when a neutralization assay was applied in a two-center seroprevalence study conducted in Novi Sad (Serbia) and Skopje (North Macedonia), no TBEV-neutralizing antibodies were found in the Serbian cohort exposed to tick bites ( Jakimovski et al, 2023 ). This result may be influenced by the small number of participants included in the Serbian cohort ( n = 51), compared with the cohort examined in this study ( n = 450).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate and implied identification of new natural foci are strongly dependent on national diagnostic guidelines and diagnostic resources [ 21 ]. Patients presenting to the hospital with a confirmed TBEV infection may play a role in detecting new natural foci, and a precise history of the medical case may generate a trace to the origin of the infection and the detection of new areas of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence in the patients who reported a tick bite was 28.9% (13/45) [ 134 ]. Recently, Jakimovski et al [ 135 ] observed that tick-infested individuals had lower seroreactivity against specific Borrelia proteins OspC and VlsE of 8.88% and 2.17%, respectively, and found TBEV-neutralizing antibodies in only one sample (2.22%) from the tick-exposed group from Skopje.…”
Section: North Macedoniamentioning
confidence: 99%